Foot Care Practices as Determinants of Diabetic Foot Ulcer Risk in Rural Populations - Ni Luh Putu Dewi Puspawati; Ni Kadek Muliawati (STIKep PPNI Jawa Barat, 2025)
Background: Diabetic foot ulcers (DFUs) represent a major chronic complication of diabetes mellitus and are associated with infection, extended hospital stays, and an increased likelihood of lower-limb amputation. Individuals with diabetes remain at lifelong risk of DFUs, with recurrence frequently reported. Consistent and appropriate foot self-care is therefore considered a key preventive measure, particularly in community settings with limited access to specialized care. Objective: This study aimed to examine the relationship between foot self-care behaviour (FSCB) and the risk of developing diabetic foot ulcers among adults with type II diabetes living in rural communities. Methods: A cross-sectional study was conducted involving 100 adult outpatients with type II diabetes attending the Sukawati II Primary Health Care Centre, Gianyar, Bali. Participants were recruited using consecutive sampling. Data were collected through structured questionnaires that included demographic characteristics and foot self-care behaviour assessed using the Nottingham Assessment of Functional Foot Care (NAFF). The risk of diabetic foot ulcers was evaluated using Inlow’s 60-second diabetic foot screening tool, incorporating a 10 g monofilament test. Data analysis employed the Gamma correlation test to determine the association between variables. Results: The findings showed that 62% of participants demonstrated poor foot self-care behaviour. Additionally, 50% of respondents were identified as being at risk of developing DFUs. Statistical analysis revealed a strong and significant inverse relationship between foot self-care behaviour and DFU risk (p = 0.001; r = −0.613). Conclusion: Poor foot self-care behaviour is strongly associated with an increased risk of diabetic foot ulcers among individuals with type II diabetes in rural settings. These findings highlight the importance of strengthening foot care education and preventive interventions at the primary health care level